2021
DOI: 10.1038/s41598-021-90947-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in a unique population of dugong (Dugong dugon) along the sea coasts of Thailand

Abstract: Dugong (Dugong dugon) populations have been shrinking globally, due in large part to habitat fragmentation, degradation and ocean pollution, and today are listed as Vulnerable by the IUCN. Thus, determining genetic diversity in the remaining populations is essential for conservation planning and protection. In this study, measures of inter-simple sequence repeat (ISSR) markers and mtDNA D-loop typing were used to evaluate the genetic diversity of 118 dugongs from skin samples of deceased dugongs collected in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…From this study, dugongs from the Andaman Sea were shown to have higher genetic diversity than those in the Gulf of Thailand, similar to data from previous inter-simple sequence repeat (ISSR) [32] and microsatellite [57] studies. In 2013, the first report of microsatellite markers (60 dugongs in the sea of Thailand between 1982-2007) found animals in the northern Andaman Sea had more genetic diversity than those in the Gulf of Thailand.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…From this study, dugongs from the Andaman Sea were shown to have higher genetic diversity than those in the Gulf of Thailand, similar to data from previous inter-simple sequence repeat (ISSR) [32] and microsatellite [57] studies. In 2013, the first report of microsatellite markers (60 dugongs in the sea of Thailand between 1982-2007) found animals in the northern Andaman Sea had more genetic diversity than those in the Gulf of Thailand.…”
Section: Discussionsupporting
confidence: 86%
“…The samples were processed using DNA extraction kits according to manufacturer's instructions (DNeasy Blood & Tissue Kit, Qiagen, Germany) at the Faculty of Veterinary Medicine, Chiang Mai University [32], and the DNA measured qualitatively and quantitatively by agarose gel electrophoresis and spectrophotometry, respectively [4].…”
Section: Dna Extractionmentioning
confidence: 99%
See 3 more Smart Citations